Comparison of the Effects of Three Different Methods in Reducing Primary Postpartum Hemorrhage - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The aim of this study was to determine the effects of three different methods in reducing primary postpartum hemorrhage. Methods: The study was carried out in Istanbul/Turkey with 150 people at a maternity hospital. The participants were assigned to the external circular fundus massage (ECFM) (n=50), external bimanual fundus compression (EBFC) (n=50) and control (C) (n=50) groups with the simple randomization method. The women in the experiment groups of external circular fundus massage or external bimanual uterus fundus compression received intervention for one hour in the postpartum period. At the 6th postpartum hour, the hemogram values and total lochia amount of all women were measured. Results: The mean +/- standard deviation (SD) age of the women was 24.77 +/- 4.40 years, 63.3% were having their first birth, and 47.3% gained weight between 11 and 16 kg in their pregnancy. There was no significant difference between the groups in terms of the mean +/- SD Hb at the 6th postpartum hour (ECFM group=11.5 +/- 1.1; EBFC Group =11.7 +/- 3.6; C group =11.4 +/- 1.0 g /dL, F= 0.371, p = 0.691). In comparison to the ECFM and C groups, the 2nd postpartum hour visual analog scale (VAS) score of the EBFC group was found to be significantly lower (p<0.05). Conclusion: The hemoglobin and thrombocyte levels at the 6th postpartum hour were higher in the EBFC group in comparison to the other groups, while the hematocrit value decreased more. Since EBFC is effective in reducing postpartum pain, it is recommended to be applied especially to women with postpartum pain.
Keywords: Hemoglobin; delivery; postpartum hemorrhage; randomized controlled; uterus massage; UTERINE SEGMENT COMPRESSION; VAGINAL DELIVERY; ACTIVE MANAGEMENT; 3RD STAGE; PREVENTION; MASSAGE; LABOR